KAJIAN PELESTARIAN DURIAN LOKAL KEDIRI MELALUI PERBANYAKAN SISTEM GRAFTING - Widyana Rahmatika; Fajar Setyawan (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2018)
The study aims to identify and characterize the local durian germplasm of Kediri to obtain durian that has the potential to be grown as a native durian of Kediri Regency and to produce seeds of local superior durian in Kediri Regency that have the potential to grow well with grafting methods. The study was conducted in Gadungan Village, Puncu District, Kediri District, 224 m asl altitude, alluvial soil type and pH 6.8, in March to September 2018. The research was factorial research using Randomized Block Design with four replications. The first factor is the variety of varieties, V1 = Kelud variety, V2 = Bokor variety. The second factor is the length of the entres, E1 = 5 cm, E2 = 7.5 cm, E3 = 10 cm. The data obtained were processed using the Analysis of Variance and continued using the BNT test. The variables observed were shoot length, number of leaves, percentage of success, when shoots broke. The results showed the best treatment in Kelud varieties with 7.5 cm and 10 cm entres length. Keywords: Durian, Grafting, Length of entres, Varieties